Alternative facts: a reconsideration of putatively natural interspecific hybrid specimens in the genus Heliconius (Lepidoptera: Nymphalidae) - Brower, Andrew V. Z. (Zootaxa, 2018)
Mallet et al. (2007 BMC Evolutionary Biology, 7, 28) employed a database of putative interspecific hybrid specimens of the genus Heliconius to advance a hypothesis of "the species boundary as a continuum." Here, each of those specimens, as well as subsequently documented specimens, is individually reassessed regarding its phenotype, potential parentage and chain of custody in collections. Using a quantified scale of reliability, most of the specimens are interpreted differently than Mallet et al.’s identifications, and the actual number of interspecific hybrids is estimated to be much smaller than they proposed. To be specific, of 163 putative hybrid specimens examined, 11% suffered from ambiguous identity, 5% from confounding issues with their data labels, 50% were arguably intraspecific (depending upon alternative species concepts), and 22% were almost certainly reared, commercial specimens. Only eleven of the specimens meet the criteria established here to be legitimate and reliable interspecific hybrids, and all of those are between closely-related species. This result has potentially important implications for current hypotheses of frequent genomic introgression of wing pattern alleles among Heliconius clades.